Changes in Body Reserves, Non-Esterified Fatty Acids, and Leptin during the Reproductive Lifespan of the Rabbit Female - Rosa Peiró; María-José Argente; María-Luz García (Animals, 2023)
The aim of this work is to study changes in body weight, perirenal fat thickness (PFT), and non-esterified fatty acid (NEFA) and leptin concentrations throughout the reproductive life of the rabbit female and their correlations when a semi-intensive reproductive rhythm is applied. A total of 46 lactating females were used. Body weight, PFT, and NEFA and leptin concentration were recorded at 12 weeks of age, at first mating and delivery, and at second, third, and fourth mating, 12th d of gestation, and delivery. The highest body weight was detected on the 12th d of any gestation, around 4280 g, and the lowest weight was at delivery, around 4030 g. PFT increased until third mating. NEFA and leptin concentration showed a cyclical pattern throughout the reproductive lifespan of the females. NEFAs presented the highest concentration at delivery within each reproductive cycle and levels decreased over the course of the deliveries (0.423 mmol/L at first delivery, 0.406 mmol/L at second delivery, 0.371 mmol/L at third delivery, and 0.309 mmol/L at fourth delivery). Similar NEFA concentrations at mating and on the 12th d of gestation were obtained. Leptin showed the highest concentrations at mating within each reproductive cycle. Leptin decreased between mating and delivery in all reproductive cycles and it was close to 1 ng/mL HE. Low or null correlations were shown between body weight, PFT, and NEFA and leptin concentration at mating, 12th d of gestation, and delivery. In conclusion, females are able to maintain a semi-intensive reproductive rhythm across four parities weighing around 4 kg from first mating. Females had an increased perirenal fat thickness until third delivery, and their NEFA concentration was maximum at delivery and leptin concentration was maximum at mating. Body weight, PFT, and NEFA and leptin concentration should be measured during critical moments of reproductive life in order to determine body condition and energy mobilization, due to their low or null correlations.